CuO-NPs Induce Apoptosis and Functional Impairment in BV2 Cells Through the CSF-1R/PLCγ2/ERK/Nrf2 Pathway - Linhui Yang; Lina Zhu; Bencheng Lin; Yue Shi; Wenqing Lai; Kang Li; Lei Tian; Zhuge Xi; Huanliang Liu (Toxics)
Copper oxide nanoparticles (CuO-NPs) induce neurological diseases, including neurobehavioral defects and neurodegenerative diseases. Direct evidence indicates that CuO-NPs induce inflammation in the central nervous system and cause severe neurotoxicity. However, the mechanism of CuO-NP-induced damage to the nervous system has rarely been studied, and the toxicity of different CuO-NP particle sizes and their copper ion (Cu2+) precipitation in microglia (BV2 cells) is worth exploring. Therefore, this study investigated CuO-NPs with different particle sizes (small particle size: S-CuO-NPs; large particle size: L-CuO-NPs), Cu2+ with equal molar mass (replaced by CuCl2 [Equ group]), and Cu2+ precipitated in a cell culture solution with CuO-NPs (replaced by CuCl2 [Pre group]), and examined the mechanism of action of each on BV2 microglia after co-culture for 12 h and 24 h. The activity of BV2 cells decreased, the morphology was damaged, and the apoptosis rate increased in all the exposed groups. Toxicity increased time- and dose-dependently, and was highest in the Equ group, followed by the S-CuO-NPs, L-CuO-NPs, and Pre groups, respectively. Subsequently, we investigated the mechanism of S-CuO-NP-induced cell injury, and revealed that S-CuO-NPs induced oxidative stress and inflammatory response and increased the membrane permeability of BV2 cells. Moreover, S-CuO-NPs reduced the ratio of p-CSF-1R/CSF-1R, p-PLCγ2/PLCγ2, p-extracellular signal-regulated kinase (ERK)/ERK, p-Nrf2/Nrf2, and Bcl-2/Bax protein expression in microglia, and elevated cleaved caspase-3 expression. The CSF-1R/PLCγ2/ERK/Nrf2 apoptotic pathway was activated. The downregulation of CX3CR1, CSF-1R, brain-derived neurotrophic factor (BDNF), and IGF-1 protein expression indicates impairment of the repair and protection functions of microglia in the nervous system. In summary, our results reveal that CuO-NPs promote an increase in inflammatory molecules in BV2 microglia through oxidative stress, activate the CSF-1R/PLCγ2/ERK/Nrf2 pathway, cause apoptosis, and ultimately result in neurofunctional damage to microglia.